Antioxidant fuel element as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411790664.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
AI Technical Summary
Existing nuclear reactor fuel elements are prone to oxidation in an oxidative atmosphere, resulting in structural integrity and performance degradation, affecting the safety of the reactor.
An antioxidant fuel element is adopted, which is composed of a fuel area, a fuel-free area and an antioxidant functional layer in sequence from the inside to the outside. The antioxidant functional layer includes at least one of a micro-four-layer SiC layer, a double-layer SiC layer, a Ti3SiC2-TiC-Si layer, a TiSi2-SiC layer, and a ZrSi2-SiC layer. Through the dense structure and material composition of these layers, the diffusion of oxidant gas is effectively slowed down.
The excellent oxidation resistance, high temperature resistance and mechanical strength of the fuel element are achieved, which significantly improves the safety of the reactor.
Smart Images

Figure CN119742092A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nuclear reactor fuel elements, and in particular, relates to a nuclear reactor anti-oxidation fuel element and a preparation method and application thereof. Background Art
[0002] Fuel elements are the core components of the reactor and the source of core energy. Their structural performance, high temperature resistance, radiation resistance and oxidation resistance are the basis for safe and efficient operation of the reactor. The direct goal of fuel element design is to produce and export fission energy most efficiently, maintain the integrity of the coating material throughout its life cycle, maximally confine the fuel and radioactive fission products, and ensure the safety of workers and the surrounding environment.
[0003] Graphite materials have outstanding advantages such as high temperature resistance, small neutron absorption cross section, stable chemical properties, and excellent high-temperature mechanical properties. They are important matrix materials and structural materials for spherical fuel elements of high-temperature gas-cooled reactors. At present, the diameter of the spherical fuel elements used in pebble-bed high-temperature gas-cooled reactors is 60 mm, including a fuel area and a fuel-free area. The spherical fuel element is a graphite matrix as a whole, and the outer layer is a fuel-free area with a thickness of about 5 mm. The basic structure is a fuel-free graphite spherical shell filled with dispersed fuel composed of coated fuel particles and graphite matrix. However, graphite materials are very sensitive to the oxidizing atmosphere in the use environment and are very easy to react with oxidizing gases above 500°C.
[0004] High-temperature gas-cooled reactors use high-purity helium as a cooling medium. Under normal service conditions, graphite is in high-purity helium. The total amount of oxidizing gas is small relative to graphite. Oxidation has little effect on the structural integrity and performance of graphite, and therefore has no significant effect on reactor performance. However, when a primary circuit rupture occurs in the reactor or a pipe rupture or even a pipe break occurs in the steam generator, air or water will enter the reactor core to varying degrees, causing graphite oxidation, which will lead to a decrease in the barrier performance of the fuel element to fission products, increase the release of fission products, and thus reduce the safety of the reactor. Therefore, improving the oxidation resistance of nuclear reactor fuel elements is of great significance to further improve the safety of nuclear reactors, and is a major research direction for the new generation of fuel elements. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides an antioxidant fuel element and a preparation method and application thereof. The antioxidant fuel element has excellent antioxidant performance, and the preparation method is simple and the cost is low. It is applicable to a variety of reactor cooling media and is of great significance to improving the safety of the reactor.
[0006] Therefore, in a first aspect of the present invention, the present invention provides an oxidation resistant fuel element, comprising:
[0007] From the inside to the outside, there are concentric axes of fuel zone, fuel-free zone and anti-oxidation functional layer; the anti-oxidation functional layer includes at least one of micro four-layer SiC layer, double-layer SiC layer, Ti3SiC2-TiC-Si layer, TiSi2-Si-SiC layer and ZrSi2-SiC layer.
[0008] According to the embodiment of the present invention, the anti-oxidation functional layer has a dense structure and its material composition has excellent anti-oxidation performance. Therefore, the anti-oxidation fuel element has excellent anti-oxidation performance, high temperature stability and mechanical strength.
[0009] In some embodiments, the grain size of the anti-oxidation functional layer is micrometer-sized;
[0010] In some embodiments, the anti-oxidation fuel element further comprises a transition layer, wherein the transition layer is located between the fuel-free zone and the anti-oxidation functional layer; the transition layer comprises a matrix material and SiC.
[0011] In some embodiments, the grain size of the transition layer is nanometer-sized;
[0012] In some embodiments, the transition layer and the anti-oxidation functional layer form a composite anti-oxidation coating, and the thickness of the composite anti-oxidation coating is 1 to 1000 μm.
[0013] In some embodiments, the fuel zone includes a matrix material and coated fuel particles, wherein the coated fuel particles are distributed in the matrix material; the fuel zone satisfies at least one of the following:
[0014] (i) The core of the coated fuel particle is at least one of UO2, UC, UN, U3Si2, and MOX;
[0015] (ii) Based on the volume of the antioxidant fuel element, the volume percentage of the coated fuel particles and the matrix material is 5 to 70%.
[0016] In some embodiments, the volume percentage of the fuel region to the fuel-free region is 10-95%.
[0017] In some embodiments, the antioxidant fuel element is a sphere or a cylinder; the diameter of the sphere is 2 to 8 cm; the diameter of the cylinder is 1 to 6 cm and the height is 1 to 3 cm.
[0018] In a second aspect of the present invention, the present invention provides a method for preparing an oxidation-resistant fuel element, comprising the following steps:
[0019] Reaction powder is used to form an anti-oxidation functional layer on the surface of a fuel element preform; the fuel element preform includes a fuel zone and a fuel-free zone which are concentric axes from the inside to the outside; the reaction powder includes at least one of Si powder, SiC powder, graphite powder for reactor, and metal powder; the method used includes at least one of an embedding method, a molten salt method, and a fluidized bed chemical vapor deposition method.
[0020] Therefore, the preparation method of the present invention has the advantages of simple process, low cost and large-scale production, and can obtain an antioxidant fuel element with excellent antioxidant performance.
[0021] In some embodiments, the method for preparing an oxidation resistant fuel element further comprises:
[0022] The fuel element preform is placed in an embedding powder for high temperature sintering to form a transition layer on the surface of the fuel element preform; the embedding powder includes at least one of SiC, Si, Al2O3 and graphite powder;
[0023] An anti-oxidation functional layer is formed on the surface of the transition layer.
[0024] In the third aspect of the present invention, the present invention proposes the use of the antioxidant fuel element of the first aspect, or the antioxidant fuel element obtained by the preparation method of the second aspect in a reactor, and the reactor includes at least one of a high-temperature gas-cooled reactor, a molten salt reactor, a fast reactor, a pressurized water reactor, a space reactor, and a micro reactor.
[0025] Therefore, the antioxidant fuel element of the present invention has excellent antioxidant performance and can meet its application in various nuclear reactors.
[0026] Compared with the prior art, the present invention has the following beneficial technical effects:
[0027] (1) The outer layer of the anti-oxidation fuel element provided by the present invention has a composite anti-oxidation coating composed of an anti-oxidation functional layer and a transition layer. The composite anti-oxidation coating has a dense structure, good high-temperature stability, high mechanical strength, and excellent anti-oxidation performance, which is of great significance to improving the safety of the reactor.
[0028] (2) The method for preparing the antioxidant fuel element provided by the present invention has the advantages of simple process, low cost and ability to achieve large-scale production.
[0029] (3) The antioxidant fuel element provided by the present invention can be used in different reactors such as high-temperature gas-cooled reactors, molten salt reactors, fast reactors, pressurized water reactors, space reactors, and micro reactors, and is suitable for a variety of reactor cooling media.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 is a cross-sectional view of a spherical and cylindrical antioxidant fuel element of the present invention;
[0033] Figure 2 is a cross-sectional view of a spherical antioxidant fuel element according to Example 1 of the present invention;
[0034] Figure 3 is a cross-sectional view of a cylindrical antioxidant fuel element according to Example 5 of the present invention;
[0035] In the figure, 1 is the fuel area; 2 is the fuel-free area; 3 is the composite anti-oxidation coating. DETAILED DESCRIPTION
[0036] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0037] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0040] In a first aspect of an embodiment of the present invention, the present invention provides an oxidation-resistant fuel element, comprising:
[0041] From the inside to the outside, there are concentric axes of fuel zone, fuel-free zone and anti-oxidation functional layer; the anti-oxidation functional layer includes at least one of micro four-layer SiC layer, double-layer SiC layer, Ti3SiC2-TiC-Si layer, TiSi2-Si-SiC layer and ZrSi2-SiC layer.
[0042] According to an embodiment of the present invention, the antioxidant fuel element is composed of a concentric fuel zone, a fuel-free zone and a composite antioxidant coating from the inside to the outside. Among them, the fuel zone is the core component in the nuclear reactor and the source of reactor energy. The fuel zone has the same shape as the fuel element. The fuel-free zone is composed of a matrix material, and its main function is to serve as a moderating material for fission neutrons and transfer the fission heat of the coated fuel particles to the surface of the fuel element. The antioxidant functional layer has a dense structure and good antioxidant properties. The material composition of the antioxidant functional layer can effectively slow down the diffusion of oxidizing gases in the layer, thereby achieving the purpose of antioxidant. Therefore, the antioxidant fuel element of the present invention has excellent antioxidant properties, high temperature stability and mechanical strength.
[0043] In some embodiments of the present invention, the grain size of the anti-oxidation functional layer is in micron order.
[0044] According to the embodiment of the present invention, the grain size of the anti-oxidation functional layer material is micrometer-level, the grain orientation is random, and the grain boundary accounts for a small proportion of the entire anti-oxidation functional layer, which can effectively slow down the diffusion of oxidizing gas in the layer and achieve the purpose of anti-oxidation. Therefore, the anti-oxidation fuel element of the present invention has excellent anti-oxidation performance.
[0045] In some embodiments of the present invention, the thickness of the anti-oxidation functional layer is 0.2-1 mm, thereby improving the anti-oxidation performance of the anti-oxidation fuel element.
[0046] As an example, the thickness of the anti-oxidation functional layer is 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, etc.
[0047] In some embodiments of the present invention, the anti-oxidation fuel element further comprises a transition layer, wherein the transition layer is located between the fuel-free zone and the anti-oxidation functional layer; the transition layer comprises a matrix material and SiC.
[0048] According to an embodiment of the present invention, the transition layer is the main heat shock resistant functional layer. Therefore, the oxidation resistant fuel element of the present invention has excellent high temperature resistance and stability.
[0049] In some embodiments of the present invention, the base material of the transition layer includes at least one of a ceramic material and a metal material.
[0050] As an example, the ceramic material includes at least one of graphite and SiC.
[0051] As an example, the metal material includes at least one of aluminum, tungsten, zirconium, and beryllium.
[0052] In some embodiments of the present invention, the grain size of the transition layer is nanometer scale.
[0053] According to the embodiment of the present invention, the grain size of the transition layer is nanometer-scale, the grain orientation of the material in the transition layer is random, and has a thermal expansion coefficient similar to that of the matrix material, which can effectively relieve the stress in the thermal shock cycle of the fuel element, and is the main thermal shock resistant functional layer. At the same time, the fine grain boundary multi-path is long, which can reduce the release of metal fission products inside the fuel element. Therefore, the oxidation-resistant fuel element of the present invention has excellent high temperature stability and mechanical strength.
[0054] In some embodiments of the present invention, the thickness of the transition layer is 0.1-300 μm, thereby further improving the high temperature stability of the anti-oxidation fuel element.
[0055] As an example, the thickness of the transition layer is 0.1 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, etc.
[0056] In some embodiments of the present invention, the transition layer and the anti-oxidation functional layer form a composite anti-oxidation coating, and the thickness of the composite anti-oxidation coating is 1 to 1000 μm, thereby further improving the anti-oxidation performance.
[0057] As an example, the thickness of the composite anti-oxidation coating is 1 μm, 100 μm, 300 μm, 500 μm, 700 μm, 900 μm, 1000 μm, etc.
[0058] In some embodiments of the present invention, the fuel zone includes a matrix material and coated fuel particles, wherein the coated fuel particles are distributed in the matrix material; the fuel zone satisfies at least one of the following:
[0059] (i) The core of the coated fuel particle is at least one of UO2, UC, UN, U3Si2, and MOX;
[0060] (ii) Based on the volume of the antioxidant fuel element, the volume percentage of the coated fuel particles and the matrix material is 5 to 70%.
[0061] According to an embodiment of the present invention, the matrix material of the fuel element has excellent high temperature resistance, is suitable for use in high temperature environments, and can provide an additional protective layer to prevent nuclear fuel leakage caused by damage to the fuel cladding, thereby improving nuclear safety. At least one of UO2, UC, UN, U3Si2, and MOX is used as the core of the coated fuel particles. Because these core materials have unique physical and chemical properties (such as high melting point, isotropy, and good irradiation stability), they are widely used in different types of nuclear reactors to improve the safety, efficiency, and economy of nuclear reactors. The use of matrix materials to coat fuel particles can effectively prevent the leakage of radioactive substances generated by the fuel particles during the reaction process, ensure nuclear safety, and improve the thermal stability of nuclear fuel.
[0062] As an example, the volume percentages are 5%, 15%, 25%, 35%, 45%, 55%, 65%, 70%, etc.
[0063] In some embodiments of the present invention, the matrix material of the fuel zone includes at least one of a ceramic material and a metal material.
[0064] As an example, the ceramic material includes at least one of graphite and SiC.
[0065] As an example, the metal material includes at least one of aluminum, tungsten, zirconium, and beryllium.
[0066] In some embodiments of the present invention, the volume percentage of the fuel area and the fuel-free area is 10-95%. There is no physical interface between the fuel area and the fuel-free area. Thus, the oxidation-resistant fuel element has better strength and thermal conductivity.
[0067] As an example, the volume percentages are 10%, 15%, 25%, 35%, 45%, 55%, 65%, 75%, 85%, 95%, etc.
[0068] In some embodiments of the present invention, the antioxidant fuel element is a sphere or a cylinder; the diameter of the sphere is 2 to 8 cm; the diameter of the cylinder is 1 to 6 cm and the height is 1 to 3 cm. Figure 1 shown.
[0069] According to an embodiment of the present invention, spherical or cylindrical fuel elements are common fuel element shapes and are widely used in different reactors such as high-temperature gas-cooled reactors, molten salt reactors, fast reactors, pressurized water reactors, space reactors, and micro reactors, and are suitable for a variety of reactor cooling media.
[0070] As an example, the diameter of the sphere is 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, etc.
[0071] As an example, the diameter of the cylinder is 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, etc.
[0072] As an example, the height of the cylinder is 1 cm, 1.5 cm, 2 cm, 2.5 cm, 3 cm, etc.
[0073] In a second aspect of the embodiments of the present invention, the present invention provides a method for preparing an oxidation-resistant fuel element, comprising the following steps:
[0074] Reaction powder is used to form an anti-oxidation functional layer on the surface of a fuel element preform; the fuel element preform includes a fuel zone and a fuel-free zone which are concentric axes from the inside to the outside; the reaction powder includes at least one of Si powder, SiC powder, graphite powder for reactor, and metal powder; the method used includes at least one of an embedding method, a molten salt method, and a fluidized bed chemical vapor deposition method.
[0075] According to the embodiments of the present invention, during the preparation process, by adjusting the material composition or ratio of the antioxidant raw materials and the treatment method, antioxidant functional layers with different material compositions can be obtained, all of which can play an excellent antioxidant function. Therefore, the preparation method of the present invention has the advantages of simple process, low cost, and large-scale production, and can obtain antioxidant fuel elements with excellent antioxidant performance.
[0076] In some embodiments of the present invention, the reaction powder of the embedding method includes at least one of Si powder, SiC powder, Al2O3 and graphite powder for reactor.
[0077] In some embodiments of the present invention, the reaction powder of the molten salt method includes: at least one of a salt mixture, Si powder, and metal powder.
[0078] As an example, the salt mixture includes at least one of NaCl, KCl, LiCl.
[0079] As an example, the metal powder includes at least one of Ti, Zr, and Nb.
[0080] In some embodiments of the present invention, the operation of the fluidized bed chemical vapor deposition method includes:
[0081] Place the sample in the graphite fluidizing tube, set the argon flow rate in the heating stage, heat it to the preset temperature, and add ZrO2 particles into the furnace through the particle sample adding device on the top of the furnace. Adjust the gas type and flow rate of each channel respectively.
[0082] Through the gas switching device, methyltrichlorosilane is carried into the furnace by hydrogen gas to carry out the deposition reaction. After the deposition reaction is completed, the sample is taken out after cooling to room temperature. During the cooling process, the gas path is kept unobstructed, and the gas setting is consistent with the heating process. The program is cooled to 1200℃, and then naturally cooled to room temperature under gas purge.
[0083] In some embodiments of the present invention, the method for preparing the oxidation-resistant fuel element further comprises:
[0084] The fuel element preform is placed in an embedding powder for high temperature sintering to form a transition layer on the surface of the fuel element preform; the embedding powder includes at least one of SiC, Si, Al2O3 and graphite powder;
[0085] An anti-oxidation functional layer is formed on the surface of the transition layer.
[0086] In some embodiments of the present invention, the high temperature sintering temperature is 1000-2300°C.
[0087] As an example, the temperature of the high temperature sintering is 1000° C., 1200° C., 1400° C., 1600° C., 1800° C., 2000° C., 2200° C., 2300° C., etc.
[0088] In some embodiments of the present invention, the method for preparing the oxidation-resistant fuel element comprises the following steps:
[0089] The matrix material and the coated fuel particles are placed in a mold for processing to form a fuel element preform; the fuel element preform comprises a fuel area and a fuel-free area which are concentric axes from the inside to the outside;
[0090] The fuel element preform is placed in the embedding powder for the first embedding and high-temperature sintering to form a transition layer on the surface of the fuel element preform to obtain a coated sample;
[0091] The coated sample is subjected to a second high-temperature treatment to form an antioxidant functional layer outside the coated sample to obtain an antioxidant fuel element.
[0092] In the third aspect of the embodiments of the present invention, the present invention proposes the use of the antioxidant fuel element of the first aspect, or the antioxidant fuel element obtained by the preparation method of the second aspect in a reactor, and the reactor includes at least one of a high-temperature gas-cooled reactor, a molten salt reactor, a fast reactor, a pressurized water reactor, a space reactor, and a micro reactor.
[0093] Therefore, the antioxidant fuel element of the present invention has excellent antioxidant performance and can meet its application in various nuclear reactors.
[0094] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0095] Embodiment 1:
[0096] An antioxidant fuel element, the preparation method of which comprises the following steps:
[0097] (1) 60% of natural flake graphite, 20% of artificial graphite and 20% of phenolic resin are uniformly mixed using a mechanical mixer as a matrix material of an antioxidant fuel element;
[0098] (2) The core of the fuel particles coated in the fuel zone is UO2;
[0099] (3) The coated fuel particles are densely packed in a circular fuel zone forming mold, and the prepared matrix material is added; the volume ratio of the coated fuel particles to the matrix material is 60%; and a metal wire is used to gently stir so that the matrix material completely penetrates into the bottom of the coated fuel particles;
[0100] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0101] (5) Place the solidified fuel zone preform into a circular fuel-free zone forming mold and adjust its position so that it is in the center of the fuel-free zone forming mold. The volume percentage of the fuel zone in the fuel element is 60%. The fuel-free zone material is the same as in step (1).
[0102] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 48 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0103] (7) The prepared fuel element preform is subjected to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 800° C. and the carbonization treatment time is 20 h; the temperature of the purification treatment is 1950° C. and the purification treatment time is 20 h.
[0104] (8) Preparing the embedding powder required for primary embedding, Si powder, SiC powder, Al2O3 and reactor graphite powder are mixed in a mass ratio of 60%, 25%, 5% and 10% to obtain the primary embedding powder.
[0105] (9) placing the fuel element preform into the primary embedding powder and sintering at 1700° C. for 2 h in an Ar gas atmosphere to obtain a one-step embedded fuel element preform;
[0106] (10) The SiC layer is deposited on the one-step embedded fuel element preform by fluidized bed chemical vapor deposition process, the deposition temperature is 1550°C, and the deposition time is 1 hour. The reactant is methyltrichlorosilane, the carrier gas is H2, and the fluidizing gas H2:Ar=9:1. The fuel element ball prepared by the embedding-fluidized bed chemical vapor deposition method is obtained.
[0107] (11) The fuel element ball prepared by the embedding-fluidized bed chemical vapor deposition method is washed and dried to obtain a spherical antioxidant fuel element with a diameter of 6 cm. The cross section of the prepared antioxidant fuel element is as follows: Figure 2 As shown, the thermal shock resistant functional layer composed of graphite and SiC is the transition layer, and the dense stacking layer composed of SiC is the anti-oxidation functional layer.
[0108] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0109] Example 2
[0110] An antioxidant fuel element, the preparation method of which comprises the following steps:
[0111] (1) Using a mechanical mixer, 55% natural flake graphite, 20% artificial graphite and 25% phenolic resin are uniformly mixed to form a matrix material for the fuel element;
[0112] (2) The core of the fuel particles in the fuel zone is UC;
[0113] (3) Pack the coated fuel particles tightly into a circular fuel zone forming mold and add the prepared matrix material. The volume ratio of the coated fuel particles to the matrix graphite is 25%; then stir lightly with a metal wire to allow the matrix material to completely penetrate the bottom of the coated fuel particles;
[0114] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0115] (5) placing the solidified fuel zone preform into a circular fuel-free zone forming mold and adjusting the position so that it is at the center of the fuel-free zone forming mold, wherein the fuel zone accounts for 45% of the volume of the fuel element, and the fuel-free zone material is the same as that in step (1);
[0116] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 35 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0117] (7) subjecting the obtained fuel element preform to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 850° C. and the carbonization treatment time is 10 h; the temperature of the purification treatment is 1850° C. and the purification treatment time is 10 h;
[0118] (8) preparing an embedding powder required for primary embedding, mixing Si powder, SiC powder, Al2O3 and reactor graphite powder in a mass ratio of 60%, 25%, 5% and 10% to obtain a primary embedding powder;
[0119] (9) placing the fuel element preform into the primary embedding powder and sintering at 1700° C. for 1 h in an Ar gas atmosphere to obtain a one-step embedded fuel element preform;
[0120] (10) preparing molten salt powder required for molten salt treatment, mixing Ti powder, NaCl and KCl in a mass ratio of 10.7%, 44.6% and 44.6% to obtain molten salt powder;
[0121] (11) placing the one-step embedded fuel element preform into the obtained molten salt powder, and performing a high-temperature sintering treatment in argon at 1100° C. for 3 h to obtain an embedded-molten salt treated fuel element ball;
[0122] (12) The fuel element ball prepared by embedding-molten salt is washed and dried to obtain a spherical anti-oxidation fuel element with a diameter of 4 cm, wherein the anti-thermal shock functional layer composed of graphite and SiC is the transition layer, and the outermost layer composed of TiSi2-Si-SiC is the anti-oxidation functional layer.
[0123] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0124] Example 3
[0125] An antioxidant fuel element, the preparation method of which comprises the following steps:
[0126] (1) 55% natural flake graphite, 25% artificial graphite and 20% phenolic resin are uniformly mixed using a mechanical mixer to form a matrix material for the fuel element;
[0127] (2) The core of the fuel particles coated in the fuel zone is U3Si2;
[0128] (3) The coated fuel particles are densely packed in a circular fuel zone forming mold, and the prepared matrix material is added; the volume ratio of the coated fuel particles to the matrix graphite is 30%; and a metal wire is used to gently stir so that the matrix material completely penetrates into the bottom of the coated fuel particles;
[0129] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0130] (5) placing the solidified fuel zone preform into a circular fuel-free zone forming mold and adjusting the position so that it is at the center of the fuel-free zone forming mold, wherein the fuel zone accounts for 60% of the volume of the fuel element, and the fuel-free zone material is the same as that in step (1);
[0131] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 48 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0132] (7) subjecting the obtained fuel element preform to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 800° C. and the carbonization treatment time is 12 h; the temperature of the purification treatment is 1900° C. and the purification treatment time is 12 h;
[0133] (8) preparing an embedding powder required for primary embedding, mixing Si powder, SiC powder, Al2O3 and reactor graphite powder in a mass ratio of 50%, 25%, 15% and 10% to obtain a primary embedding powder;
[0134] (9) placing the fuel element preform into the primary embedding powder, and sintering at 1700° C. for 3 h in an Ar gas atmosphere to obtain a one-step embedded fuel element preform;
[0135] (10) preparing the embedded molten salt powder required for the molten salt, mixing NaCl, KCl and Ti powder in a mass ratio of 20%, 40% and 40% to obtain a molten salt powder;
[0136] (11) placing the fuel element preform into molten salt powder and sintering at 1100° C. for 2 h in a vacuum atmosphere to obtain a fuel element ball prepared by the embedding-molten salt method;
[0137] (12) The fuel element ball prepared by the embedding-molten salt method is washed and dried to obtain a spherical anti-oxidation fuel element with a diameter of 4 cm, wherein the thermal shock resistant functional layer composed of graphite and SiC is the transition layer, and the outermost layer composed of Ti3SiC2-TiC-SiC is the anti-oxidation functional layer.
[0138] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0139] Example 4
[0140] An antioxidant fuel element, the preparation method of which comprises the following steps:
[0141] (1) Using a mechanical mixer, 65% natural flake graphite, 15% artificial graphite and 20% phenolic resin are uniformly mixed to form a matrix material for the fuel element;
[0142] (2) The core of the fuel particles coated in the fuel zone is UO2;
[0143] (3) The coated fuel particles are densely packed in a circular fuel zone forming mold, and the prepared matrix material is added; the volume ratio of the coated fuel particles to the matrix graphite is 50%; and a metal wire is used to gently stir so that the matrix material completely penetrates into the bottom of the coated fuel particles;
[0144] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0145] (5) placing the solidified fuel zone preform into a circular fuel-free zone forming mold and adjusting the position so that it is at the center of the fuel-free zone forming mold, wherein the fuel zone accounts for 50% of the volume of the fuel element, and the fuel-free zone material is the same as that in step (1);
[0146] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 48 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0147] (7) subjecting the obtained fuel element preform to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 850° C. and the carbonization treatment time is 5 h; the temperature of the purification treatment is 1850° C. and the purification treatment time is 5 h;
[0148] (8) preparing an embedding powder required for primary embedding, mixing Si powder, SiC powder, Al2O3 and reactor graphite powder in a mass ratio of 55%, 20%, 10% and 15% to obtain a primary embedding powder;
[0149] (9) placing the fuel element preform into the primary embedding powder and sintering at 1700° C. for 2 h in an Ar gas atmosphere to obtain a one-step embedded fuel element preform;
[0150] (10) preparing an embedding powder required for secondary embedding, mixing Zr powder, Si powder and reactor graphite powder in a mass ratio of 8%, 30% and 62% to obtain a secondary embedding powder;
[0151] (11) placing the one-step embedded fuel element preform into the secondary embedded powder, and sintering at 1800° C. for 4 h in a vacuum atmosphere to obtain a two-step embedded fuel element ball;
[0152] (12) The fuel element ball prepared by the two-step embedding method is washed and dried to obtain a spherical antioxidant fuel element with a diameter of 5 cm, wherein the thermal shock resistant functional layer composed of graphite and SiC is the transition layer, and the outermost layer composed of ZrSi2-SiC is the antioxidant functional layer.
[0153] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0154] Example 5
[0155] An antioxidant fuel element, the preparation method of which comprises the following steps:
[0156] (1) Using a mechanical mixer, 65% natural flake graphite, 15% artificial graphite and 20% phenolic resin are uniformly mixed to form a matrix material for the fuel element;
[0157] (2) The core of the fuel particles coated in the fuel zone is UO2;
[0158] (3) The coated fuel particles are densely packed in a circular fuel zone forming mold, and the prepared matrix material is added; the volume ratio of the coated fuel particles to the matrix graphite is 50%; and a metal wire is used to gently stir so that the matrix material completely penetrates into the bottom of the coated fuel particles;
[0159] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0160] (5) placing the solidified fuel zone preform into a circular fuel-free zone forming mold and adjusting the position so that it is at the center of the fuel-free zone forming mold, wherein the fuel zone accounts for 50% of the volume of the fuel element, and the fuel-free zone material is the same as that in step (1);
[0161] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 48 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0162] (7) subjecting the obtained fuel element preform to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 850° C. and the carbonization treatment time is 5 h; the temperature of the purification treatment is 1850° C. and the purification treatment time is 5 h;
[0163] (8) preparing an embedding powder required for primary embedding, mixing Si powder, SiC powder, Al2O3 and reactor graphite powder in a mass ratio of 55%, 20%, 10% and 15% to obtain a primary embedding powder;
[0164] (9) placing the fuel element preform into the primary embedding powder and sintering at 1700° C. for 2 h in an Ar gas atmosphere to obtain a one-step embedded fuel element preform;
[0165] (10) preparing an embedding powder required for secondary embedding, mixing Si powder, Al2O3 and reactor graphite powder in a mass ratio of 80%, 2% and 18% to obtain a secondary embedding powder;
[0166] (11) placing the one-step embedded fuel element preform into the secondary embedded powder, and sintering at 1800° C. for 4 h in a vacuum atmosphere to obtain a two-step embedded fuel element ball;
[0167] (12) The fuel element ball prepared by the two-step embedding method is washed and dried to obtain a cylindrical antioxidant fuel element with a diameter of 3 cm and a height of 2 cm. The cross-sectional view of the prepared antioxidant fuel element is as follows: Figure 3 Among them, the thermal shock resistant functional layer composed of graphite and SiC is the transition layer, and the outermost layer of the micro four-layer SiC composed of SiC fine grain layer, SiC dense body layer, SiC and Si free stacking layer is the anti-oxidation functional layer.
[0168] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0169] Comparative Example 1:
[0170] A fuel element, the preparation method of which comprises the following steps:
[0171] (1) Using a mechanical mixer, 65% natural flake graphite, 15% artificial graphite and 20% phenolic resin are uniformly mixed to form a matrix material for the fuel element;
[0172] (2) The core of the fuel particles coated in the fuel zone is UO2;
[0173] (3) The coated fuel particles are densely packed in a circular fuel zone forming mold, and the prepared matrix material is added; the volume ratio of the coated fuel particles to the matrix graphite is 50%; and a metal wire is used to gently stir so that the matrix material completely penetrates into the bottom of the coated fuel particles;
[0174] (4) placing the fuel region forming mold in a drying oven at 85° C. for heating and curing for 24 hours, taking it out, and breaking the fuel region forming mold after cooling to obtain a fuel region preform;
[0175] (5) placing the solidified fuel zone preform into a circular fuel-free zone forming mold and adjusting the position so that it is at the center of the fuel-free zone forming mold, wherein the fuel zone accounts for 50% of the volume of the fuel element, and the fuel-free zone material is the same as that in step (1);
[0176] (6) placing the fuel-free zone forming mold in a drying oven at 100° C. for heating and curing for about 48 hours, taking it out, and breaking the fuel-free zone forming mold after cooling to obtain a fuel element preform;
[0177] (7) subjecting the obtained fuel element preform to heat treatment, including carbonization treatment and purification treatment: the temperature of the carbonization treatment is 850° C. and the carbonization treatment time is 5 h; the temperature of the purification treatment is 1850° C. and the purification treatment time is 5 h;
[0178] The mold was replaced and antioxidant graphite balls with a diameter of 15 mm were prepared according to the above method, and their oxidation weight loss rate was tested.
[0179] Oxidation weight loss rate test:
[0180] The antioxidant graphite balls prepared in the above examples were weighed respectively, and then placed in a muffle furnace, heated to 1500° C., kept warm for 200 hours, taken out, cooled to room temperature, and weighed again to measure the oxidation weight loss rate. The results are shown in Table 1.
[0181] Table 1 Oxidation weight loss test results of Examples 1-5
[0182] Group Preparation method of composite anti-oxidation coating Composite anti-oxidation coating Quality Change Example 1 Embedding-Fluidized Bed Chemical Vapor Deposition Double layer SiC / SiC Increase 1.95wt% Example 2 Embedding-molten salt method <![CDATA[TiSi2-Si-SiC / SiC]]> Reduction of 0.96wt% Example 3 Embedding-molten salt method <![CDATA[Ti3SiC2-TiC-Si / SiC]]> Reduction 1.02wt% Example 4 Two-step embedding method <![CDATA[ZrSi2-SiC / SiC]]> Increase 1.69wt% Example 5 Two-step embedding method Micro Four-layer SiC / SiC Increase 0.52wt% Comparative Example 1 none none Reduce 50.00wt%
[0183] As shown in Table 1, the mass changes of Examples 1-5 are small, indicating that Examples 1-5 have good anti-oxidation performance. The fuel element of Comparative Example 1 is prone to oxidation weight loss due to the lack of composite anti-oxidation coating, resulting in a 50% reduction in mass. Therefore, it is shown that the composite anti-oxidation coating of the anti-oxidation fuel element of the present invention has an excellent anti-oxidation effect.
[0184] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0185] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An oxidation-resistant fuel element, characterized in that: include: From the inside to the outside, there are concentric axes of fuel zone, fuel-free zone and anti-oxidation functional layer; the anti-oxidation functional layer includes at least one of a micro four-layer SiC layer, a double-layer SiC layer, a Ti3SiC2-TiC-Si layer, a TiSi2-Si-SiC layer, and a ZrSi2-SiC layer.
2. The oxidation-resistant fuel element according to claim 1, characterized in that: The grain size of the anti-oxidation functional layer is micron-level.
3. The oxidation-resistant fuel element according to claim 1, characterized in that: The anti-oxidation fuel element further comprises a transition layer, wherein the transition layer is located between the fuel-free zone and the anti-oxidation functional layer; the transition layer comprises a matrix material and SiC.
4. The oxidation-resistant fuel element according to claim 3, characterized in that: The grain size of the transition layer is nanometer level.
5. The oxidation-resistant fuel element according to claim 3, characterized in that: The transition layer and the anti-oxidation functional layer form a composite anti-oxidation coating, and the thickness of the composite anti-oxidation coating is 1 to 1000 μm.
6. The oxidation-resistant fuel element according to claim 1, characterized in that: The fuel zone comprises a matrix material and coated fuel particles, wherein the coated fuel particles are distributed in the matrix material; the fuel zone satisfies at least one of the following: (i) the core of the coated fuel particle is at least one of UO2, UC, UN, U3Si2, and MOX; (ii) Based on the volume of the antioxidant fuel element, the volume percentage of the coated fuel particles to the matrix material is 5-70%.
7. The oxidation resistant fuel element according to claim 1, characterized in that: The volume percentage of the fuel area and the fuel-free area is 10-95%.
8. The oxidation resistant fuel element according to claim 1, characterized in that: The antioxidant fuel element is a sphere or a cylinder; the diameter of the sphere is 2 to 8 cm; the diameter of the cylinder is 1 to 6 cm, and the height is 1 to 3 cm.
9. A method for preparing an oxidation-resistant fuel element, characterized in that: The following steps are involved: Reaction powder is used to form an anti-oxidation functional layer on the surface of a fuel element preform; the fuel element preform includes a fuel zone and a fuel-free zone which are concentric axes from the inside to the outside; the reaction powder includes at least one of Si powder, SiC powder, graphite powder for reactor, and metal powder; the method used includes at least one of an embedding method, a molten salt method, and a fluidized bed chemical vapor deposition method.
10. The preparation method according to claim 9, characterized in that: Also includes: The fuel element preform is placed in an embedding powder for high temperature sintering to form a transition layer on the surface of the fuel element preform; the embedding powder comprises at least one of SiC, Si, Al2O3 and graphite powder; An anti-oxidation functional layer is formed on the surface of the transition layer.
11. Use of the antioxidant fuel element according to any one of claims 1 to 8, or the antioxidant fuel element obtained by the preparation method according to any one of claims 9 to 10 in a reactor, wherein the reactor includes at least one of a high temperature gas-cooled reactor, a molten salt reactor, a fast reactor, a pressurized water reactor, a space reactor, and a micro reactor.
Citation Information
Patent Citations
SiC / SiO2 composite high-temperature oxidation resistant coating prepared from surface of graphite material at reactor and composite material
CN104609896A
Method for preparing SiC coating on surface of spherical graphite material
CN105130506A
Corrosion and wear resistant coating on zirconium alloy cladding
CN108140434A
Composite high-temperature anti-oxidation coating of graphite material for nuclear reactor and preparation method of composite high-temperature anti-oxidation coating
CN113526983A
Wear-resistant and oxidation-resistant coating on the surface of spherical fuel elements and its preparation method
CN114937514A